LINGUISTIC AND CULTURAL ANALYSIS OF THE CONCEPT OF HAPPINESS IN ENGLISH AND UZBEK LANGUAGES - Ashurokhunova Dildora Toxir qizi (TADQIQOTLAR.UZ, 2024)
Abstract: This article aims to explore the concept of happiness from linguistic and cultural perspectives in both the English and Uzbek languages. The study will analyze how happiness is expressed, perceived, and valued in these two distinct linguistic and cultural contexts, shedding light on the similarities and differences in the conceptualization of happiness.